Assistive Technology to Enhance Access to Information for Student with Disabilities: A Case Study in Surabaya - Fitri Mutia; Indah Rachma Cahyani (Program Studi Ilmu Perpustakaan UIN Alauddin, 2021)
Access to information becomes an important means of achieving success in various aspects of life. Thus, it is considered the rights of every citizen without being impeded by physical or mental limitations. This study aims to analyze access to information that supports students with visual impairments (blind) in conducting learning activities at the university. This research was conducted at the Social and Political Sciences Faculty of Universitas Airlangga (Unair) Surabaya, involving 11 informants, three of whom are visually impaired students (blind) in the faculty. The results of this study indicate that according to three of the visually impaired informants the assistive technologies they used to support their learning processes, such as mobile phones, laptops, scanners, and recording devices, were provided independently. The technology is very helpful for them to obtain information validly and quickly, as well as to understand the contents of the information more easily and assist them to share the information with other colleagues. The supporting informants are 3 lecturers from the Faculty of Social and Political Sciences of Universitas Airlangga who teach visually impaired students, 3 friends of the main informant, 1 university representative, and 1 faculty representative. This paper uses an interpretive paradigm, which aims to analyze a social reality and how that reality is formed. This research uses a qualitative type that seeks to understand social or human problems, based on the creation of a complete holistic picture that is formed with words, reports the views of informants in detail, and arranged in a natural setting.